2020
DOI: 10.1111/jfbc.13177
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fats promote inflammation in Wistar rats as well as induce proliferation, invasion of SKOV3 ovarian cancer cells

Abstract: The role of high fat diet (HFD) in ovarian cancer and its underlying mechanisms are poorly known. In current investigation, we investigated inflammatory and oncogenic effect of dietary fats in female Wistar rats and ovarian cancer cell line (SKOV3). The ELISA kits were used for adipokines and inflammatory factors analyses in sera collected from rats fed with high fat diet (SR‐HFD). Cell growth, proliferation, apoptosis, migration, and invasion were measured in SKOV3 cells treated with the SR‐HFD and FA mix. IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…A diet high in oil, fat, and salt is also undesirable. A study on animals subjected to a high-fat diet reported the diet may promote the development of ovarian cancer by disrupting the levels of inflammatory factors ( 39 ). Therefore, poor diet and health habits are crucial risk factors for the occurrence of cancer.…”
Section: Gynecologic Malignancies and Gmmentioning
confidence: 99%
“…A diet high in oil, fat, and salt is also undesirable. A study on animals subjected to a high-fat diet reported the diet may promote the development of ovarian cancer by disrupting the levels of inflammatory factors ( 39 ). Therefore, poor diet and health habits are crucial risk factors for the occurrence of cancer.…”
Section: Gynecologic Malignancies and Gmmentioning
confidence: 99%
“…Several potential mechanisms underlie this relationship, including metabolic alterations, immune microenvironment modulation, and chronic low‐grade inflammation due to obesity. Diet also contributes to inflammation as a high‐fat diet has been shown to enhance ovarian cancer progression and upregulate inflammatory markers IL‐6, IL‐1β, and TNFα 135 . Estrogen‐mediated signaling via ERα also links obesity to ovarian cancer as ovaries are both the primary producers and targets of estrone (E1) and estradiol (E2).…”
Section: Methodsmentioning
confidence: 99%
“…Diet also contributes to inflammation as a high‐fat diet has been shown to enhance ovarian cancer progression and upregulate inflammatory markers IL‐6, IL‐1β, and TNFα. 135 Estrogen‐mediated signaling via ERα also links obesity to ovarian cancer as ovaries are both the primary producers and targets of estrone (E1) and estradiol (E2). ERα activation enhances downstream upregulation of proteins involved in cell proliferation, motility, and invasion.…”
Section: Methodsmentioning
confidence: 99%
“…Uncoated and Ch-AgNPs were evaluated for their antiproliferative activity on HT29 colorectal cancer cell line by (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) assay (Saeidi et al, 2020). Cells were seeded at a density of 1x10 4 cells/well in 96-well plates and were cultured in DMEM medium supplemented with 10% FBS and 1% pen-strept solution at 37°C in 5% CO2.…”
Section: Determining Antiproliferative Activity Of Nps and Ch-agnpsmentioning
confidence: 99%